Maslahah and Sakinah Family's Review of Marriage Through Marriage Dispensation in Central Lampung Regency - Iim Fahimah; Zaenal Zaenal (Fakultas Syariah UIN Fatmawati Sukarno Bengkulu, 2022)
Some couples are not of legal age who have received a marriage dispensation. A search was conducted on their post-marriage conditions. Whether this early life is subjected to separation or is it precisely harmonious. The authors researched couples who married through the marriage dispensation route in Central Lampung Regency. How do maslahah and sakinah families review the marriage through the marriage dispensation route in Lampung Tengah Regency? Marriage through the marriage dispensation route in central Lampung Regency is in the review of Maslahah and the sakinah family that their marriage is classified as a group of Sakinah II families bringing benefits to their households. In general, the values of the maslahat are obtained in three stages; the benefit obtained at the time of the implementation of the marriage dispensation took place, by obtaining the legality of the couple's conjugal relationship has been valid. The benefit in their home life is due to their good and harmonious relationship, and can be beneficial for those around them. The future benefit of the couple's household and their future child, due to their legal marriage. Terdapat pasangan yang belum cukup usia pernikahan yang mendapatkan penetapan dispensasi pernikahan. Penelusuran dilakukan tentang kondisi pasca pernikahan mereka. Apakah kehidupan usia dini ini mengalami perpisahan atau justru harmonis. Penulis melakukan penelitian pasangan yang menikah dengan melalui jalur dispensasi pernikahan di Kabupaten Lampung Tengah. Bagaimana tinjauan maslahah dan keluarga sakinah terhadappernikahan melaui jalur dispensasi nikah di Kabupaten Lampung Tengah? Pernikahan melalui jalur dispensasi nikah di Kabupaten Lampung tengah dalam tinjauan Maslahah dan keluarga sakinah bahwa pernikahan mereka tergolong kelompok Keluarga Sakinah II membawa kemaslahan bagi rumah tangganya. Secara umum nilai-nilai maslahat tersebut diperoleh dalam tiga tahapan; kemaslahatan yang diperoleh pada saat pelaksanaan dispensasi nikah berlangsung, dengan memperoleh legalitas hukum dari hubungan suami istri pasangan tersebut telah sah. Kemaslahatan di dalam kehidupan rumah tangganya karena hubungan mereka yang baik dan harmonis, serta dapat bermanfaat untuk orang di sekitarnya. Kemaslahatan yang bersifat masa depan rumah tangga pasangan tersebut dan anak mereka di masa depan, karena pernikahannya yang legal.